2000
DOI: 10.4049/jimmunol.165.3.1470
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD8 Attenuates Cytotoxic T Cell Responses Against Replication-Defective Adenovirus Affording Transprotection of Transgenes In Vivo

Abstract: The T cell coreceptor, CD8, enhances T cell-APC interactions. Because soluble CD8α homodimers can antagonize CD8 T cell activation in vitro, we asked whether secretion of soluble CD8 would effect cytotoxic T cell responses in vivo. Production of soluble CD8 by a replication-defective adenovirus vector allowed persistent virus expression for up to 5 mo in C57BL/6 mice and protected a second foreign transgene from rapid deletion. Soluble CD8 selectively inhibited CD8 T cell proliferation and IFN-γ production and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 49 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…All viruses used in this study, including Ad null, lacked E1 and E3 (Ad type 5) and were replication defective (20). Ad type 5 expressing the ectodomain of murine CD8-␣ (Ly2.1) or chloramphenicol acetyltransferase (CAT) (AdsCD8 or AdCAT) was produced as described elsewhere (20).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All viruses used in this study, including Ad null, lacked E1 and E3 (Ad type 5) and were replication defective (20). Ad type 5 expressing the ectodomain of murine CD8-␣ (Ly2.1) or chloramphenicol acetyltransferase (CAT) (AdsCD8 or AdCAT) was produced as described elsewhere (20).…”
Section: Methodsmentioning
confidence: 99%
“…Unlike these two strains of mice however, BALB/c mice rapidly eliminated the Ad vector expressing sCD8. Paradoxically, in vitro studies revealed that splenic T cells obtained from BALB/c mice were less activated and exhibited less antigen-specific cytotoxicity after restimulation compared to B6 mice (20). This finding suggested that the rapid extinction of transgene expression was most likely facilitated by non-CD8 effector cell(s).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…20 Additional strategies being evaluated to attenuate the host antiadeno response include serotype switching 21,22 and the coadministration of immunosuppressants. 3,[23][24][25] In addition to quantitating the T-cell response to adenovirus epitopes in vitro using the ELISPOT assay, we developed a semiquantitative method to assess the strength of the T-cell response to adenovirus in vivo. The use of Ad5SEAP in Jh mice is a highly effective assay for measuring the effects of adenovirus T-cell responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…1A). This is likely due to the fact that BALB/c inbred mice eliminate cells containing the Ad transgene much more rapidly than do C57BL/6 mice (23,24). While 4 of 15 BALB/cJ mice had milligram per milliliter levels of VNA, the rest had levels of 1 to 100 g/ml.…”
Section: Resultsmentioning
confidence: 90%